To change the world : the irony, tragedy, and possibility of Christianity in the late modern world - Hunter, James Davison, 1955- (New York : Oxford University Press, 2010)
The call to make the world a better place is inherent in the Christian belief and practice. This book looks at why efforts to change the world by Christians so often fail or have gone tragically awry and how Christians in the 21st century might live in ways that have integrity with their traditions and are more transformative. The author appraises the most popular models of world-changing among Christians today, highlighting the ways they are inherently flawed and therefore incapable of generating the change to which they aspire. Because change implies power, all Christians eventually embrace strategies of political engagement. He offers a trenchant critique of the political theologies of the Christian Right and Left and the Neo-Anabaptists, taking on many respected leaders, from Charles W. Colson to Jim Wallis and Stanley Hauerwas. He argues that all too often these political theologies worsen the very problems they are designed to solve. What is really needed is a different paradigm of Christian engagement with the world, one that Hunter calls "faithful presence"--an ideal of Christian practice that is not only individual but institutional; a model that plays out not only in all relationships but in our work and all spheres of social life. He offers real life examples, large and small, of what can be accomplished through the practice of faithful presence. Such practices will be more fruitful, he argues, more exemplary, and more deeply transfiguring than any more overtly ambitious attempts can ever be.
Christian faith and the task of world-changing -- Culture: the common view -- The failure of the common view -- An alternative view of culture and cultural change in eleven propositions -- Evidence in history -- The cultural economy of American Christianity -- For and against the mandate of creation -- The problem of power -- Power and politics in American culture -- The Christian Right -- The Christian Left -- The neo-Anabaptists -- Illusion, irony, and tragedy -- Rethinking power: theological reflections -- The challenge of faithfulness -- Old cultural wineskins -- The groundwork for an alternative way -- Toward a theology of faithful presence -- The burden of leadership: a theology of faithful presence in practice -- Toward a new city commons.
Includes bibliographical references (p. [337]-344) and index.
Keywords: Church and the world; Christianity -- United States